FACTORS OF PERSONALITY’S DEVELOPMENT OF LAW ENFORSMENT OFFICERS IN THE CONDITIONS OF TRAINING IN HIGHER EDUCATIONAL INSTITUTIONS - Shvets, Dmitro (PSYCHOLOGICAL JOURNAL, 2016)
The article deals with factors of personality’s development of law enforcement officers in the conditions of training in higher educational institutions. The vast majority of scientists noted the close relationship of the personality’s development with the change of the leading type of activity, which makes the basic psychological personality changes. On the stage of the reform of departmental education one of the important directions of development of higher education is a science-based activity for the training and education of law enforcement professionals in higher educational institutions of MIA of Ukraine. The primary institution of socialization of future police officer becomes higher educational institution of MIA of Ukraine. It is shown that the person of cadets besides the specifics of education in institutions of system of the Ministry of Interior of Ukraine, influenced by a number of features inherent in the student’s age. The genesis of new psychic structures of student’s age caused to a great extent of environmental influences. Analysis of psychological studies reveals the following factors of personality’s development of a cadet in the conditions of training in higher educational institutions: assertiveness, professional identity, professional consciousness, self-actualization, social competence, “Self-concept”; meaning-life orientation, values, motivation, cognitive styles, professionally significant qualities, principles and form of education, factors of professional burnout and maladjustment. Personality’s development of future law enforcement officers in higher education institutions of Ministry of Internal Affairs of Ukraine is determined by a complex of internal and external conditions, namely: features of adolescence, the status of the cadet, features of training on different courses, orientation of professional training, personality’s development of the future police officers, which is provided by the activation of their own ability for self-discovery and reflection.